"A Rose by Any Other Name": On Ways of Approaching Discourse Analysis. Issue 1 (2nd April 2018) - Carta, Caterina
Abstract: Discourse analysis offers an extremely diversified landscape, spanning time and disciplines far beyond the field of international relations (IR). With a rich lineage, it comes as no surprise that under the label "Discourse Analysis" (DA) one cannot find a unified theoretical family within IR but rather a plurality of heterogeneous ways of approaching discourse analysis. By leveraging the wealth of discourse analytical works accumulated over more than three decades, this article intends to discuss some of the main theoretical tenets of three competing perspectives on discourse analysis (PDAs): constructivism, critical realism and poststructuralism. It does so by tracing their links to their respective putative philosophical referents. Distinct from Milliken (1999), who consciously stresses the commonalities between various PDAs, this contribution identifies the differences between them. The paper proceeds as follows. First, it locates IR PDAs in the framework of debates over the core branches of the philosophy of social science. Constructivist, poststructuralist and critical realist PDAs will be located along both a foundational/nonfoundational ontological continuum and a positivist/post-positivist epistemological continuum. Secondly, it retraces the main tenets of post-structuralist, constructivist, and critical realist PDAs to discourse by identifying the relevant debates that have characterized the approach to discourse analysis in IR. Finally, it presents some methodological guidelines and provides examples on how DA endeavors have been practiced.